Serum neurofilament light chain in response to probiotics in bi-center, double-blind, randomized, placebo-controlled clinical trial (CleverAge Biota) - Fialova, Lenka; Bartos, Ales; Kalousova, Marta; Noskova, Libuse; Zelenkova, Miroslava; Slukova, Michaela; Zima, Tomas (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2025)
BACKGROUND AND AIMS: Neurodegenerative disorders affecting the brain and spinal cord are caused by a large number of factors. More recently, imbalances in gut microbiota are found to be one factor linked directly to neurological dysfunction. Probiotics prevent cognitive decline. For the first time, the effect of probiotics was assessed by monitoring the concentrations of the neurodegeneration biomarker neurofilament light chains (NfL) in a well-defined group of community-dwelling individuals. The aim of this study was to determine whether administration of our new probiotics could reduce NfL concentrations. METHODS: The serum NfL concentrations were measured in total of 190 serum samples of 85 older community-dwelling individuals. The participants were randomly divided into two groups: the PROPLA group and the PLAPRO group. Individuals in the PROPLA group started with a three-month use of probiotics and continued with a three-month use of placebo while the order was reversed in the PLAPRO group. The participants underwent detailed examinations at three time points: at baseline, in three and six months. The serum NfL concentrations were determined using ultrasensitive single-molecule array (SIMOA) assay. RESULTS: Longitudinal comparisons of NfL concentrations between samplings at different time points in the PROPLA and PLAPRO groups showed no statistically significant differences. Baseline NfL concentrations at the beginning of the study and in the succeeding samplings were not significantly different for the two groups in cross-sectional comparisons. CONCLUSIONS: Serum NfL concentrations were not influenced by the three-month use of probiotics.
Keywords: serum; Male; biologické markery; neurofilament light chain; Biomarkers; probiotika; Aged; Gastrointestinal Microbiome; mužské pohlaví; senioři; cognition; střevní mikroflóra; Neurofilament Proteins; dvojitá slepá metoda; senioři nad 80 let; lidé; ženské pohlaví; Humans; gastrointestinal microbiome; Aged, 80 and over; Probiotics; probiotics; Double-Blind Method; Female; lidé středního věku; neurofilamentové proteiny; Middle Aged